2018
DOI: 10.1159/000486033
|View full text |Cite
|
Sign up to set email alerts
|

Low FT4 Concentrations around the Start of Recombinant Human Growth Hormone Treatment: Predictor of Congenital Structural Hypothalamic-Pituitary Abnormalities?

Abstract: Background: Growth hormone (GH) treatment may unmask central hypothyroidism (CeH). This was first observed in children with GH deficiency (GHD), later also in adults with GHD due to acquired “organic” pituitary disease. We hypothesized that newly diagnosed CeH in children after starting GH treatment for nonacquired, apparent isolated GHD points to congenital “organic” pituitary disease. Methods: Nationwide, retrospective cohort study including all children with nonacquired GHD between 2001 and 2011 in The Neth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…This development implies either a genetically determined vulnerability or masked insufficiency of pituitary or hypothalamic cells or an acquired damage of the hypothalamic-pituitary axis with progressive dysfunction. Treatment with recombinant human GH (rhGH) may unmask TSH deficiency in some patients with GHD [ 2 ]. Additional pituitary deficits also arise over time in monogenic hypopituitarism caused by mutations in PROP1 , POU1F1 , HESX1 , and other developmental genes [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This development implies either a genetically determined vulnerability or masked insufficiency of pituitary or hypothalamic cells or an acquired damage of the hypothalamic-pituitary axis with progressive dysfunction. Treatment with recombinant human GH (rhGH) may unmask TSH deficiency in some patients with GHD [ 2 ]. Additional pituitary deficits also arise over time in monogenic hypopituitarism caused by mutations in PROP1 , POU1F1 , HESX1 , and other developmental genes [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thyroid-stimulating hormone (TSH) deficiency is the most frequent secondary pituitary hormone deficiency in children initially diagnosed with GHD, with a reported prevalence of 6.3% during the first 2 years of treatment [ 2 ]. The clinical characteristics of TSH deficiency are milder than in primary hypothyroidism.…”
Section: Introductionmentioning
confidence: 99%
“…With the current study, we visualized the FP that was referred due to a T4/TBG ratio ≤17 (n = 1,196 Although the large number of false-positive referrals (low specificity) forms the major drawback of the current NBS algorithm to detect also CH-C patients, it should be noted that between 1995 and 2015 per year on average 0.8 patients with CH-C were missed by NBS (unpublished data from a national voluntary registration for pediatric disorders). In addition, in a recent study, we showed that this number may be even higher (2-3 missed CH-C patients per year) [11]. Hence, the sensitivity of the Dutch screening algorithm to detect CH-C patients is not 100%.…”
Section: Discussionmentioning
confidence: 80%
“…The actual false-negative count is likely to be higher, as also CH-C, central congenital hypothyroidism; CH-T, thyroidal congenital hypothyroidism; ELISA, enzyme-linked immuno sorbent assay; PPV, positive predictive value; RIA, radio-immunoassay; T4, total thyroxine; TBG, thyroxine-binding globulin. suggested in a study showing the occurrence of (probable) CH-C after initiation of growth hormone treatment in children with congenital growth hormone deficiency (15). Our unique stepwise T4-TSH-TBG NBS algorithm resulted in a PPV of 21.0%.…”
Section: Discussionmentioning
confidence: 82%